Effectiveness of edaravone in preventing contrast‐induced nephropathy in high‐risk patients undergoing coronary angiography: A randomized, double‐blind trial - Azam Esmailnejad; Sepideh Zununi Vahed; Seyyedeh Mina Hejazian; Naser Aslanabadi; Hassanali Lotfollahhi Gharakhanlu; Majid Saraei; Ahmad Ahmadzadehpournaky; Kasra Ardalan; Mohammadreza Ardalan; Samad Ghaffari Bavil (Wiley, 2024)
Abstract Contrast‐induced nephropathy (CIN) is a serious complication that occurs subsequent to the administration of contrast media for therapeutic angiographic interventions. As of present, no effective therapy exists to prevent its occurrence. This single‐center double‐blind randomized controlled trial aimed to evaluate the effect of edaravone, an antioxidant, in a group of high‐risk patients undergoing coronary angiography. Ninety eligible patients with chronic kidney disease Stages 3-4 were randomly assigned to either the control group (n = 45) or the intervention group (n = 45). In the intervention group, one dosage of edaravone (60 mg) in 1 L of normal saline was infused via a peripheral vein 1 h prior to femoral artery‐directed coronary angiography. Patients in the control group received an equal amount of infusion in their last hour before angiography. Both groups received intravenous hydration with 0.9% sodium 1 mL/kg/h starting 12 h before and continuing for 24 h after angiography. The primary outcome measure was the onset of CIN, defined as a 25% increase in serum creatinine levels 120 h after administration of contrast media. The occurrence of CIN was observed in 5.5% (n = 5) of the studied population: 2.2% of patients in the intervention group (n = 1) and 8.9% of controls (n = 4). However, this difference was not statistically significant. Administration of a single dosage of edaravone 1 h prior to infusion of contrast media led to a reduction in the incidence of CIN. Further investigations, employing larger sample sizes, are warranted to gain a comprehensive understanding of its efficacy.